Comparative study between self-perception of cutaneous characteristics and the Baumann form (Research, Society and Development, 2023)
The present study aimed to observe the self-knowledge of the selected population in relation to the types of skin presented by residents of the state of Sergipe, within the age group of 20 to 60 years, of both sexes and different ethnicities. For this, the Baumann questionnaire was applied to the volunteers, developed by the dermatologist Leslie Baumann in the USA and composed of 64 questions that classify the skin in relation to hydration, sensitivity, pigmentation and tendency to wrinkles. The initial results show that there is a predominance, among those assessed, of people with sensitive, oily skin, with a low level of pigmentation and a tendency to wrinkles. Considering the high miscegenation in the state of Sergipe, as a result of the colonial period, and the characteristics of most of the assessed population, the present study highlights the importance of general care for this population.